O Projeto Político Pedagógico e sua inter-relação com os princípios da gestão democrática: uma análise em uma escola pública municipal de São Luís - MA - Oliveira, Paulo Ricardo Amaral (2022)
This research is part of the Graduate Program in Education - PPGE of the State University of Maranhão - UEMA, and is entitled "THE POLITICAL PEDAGOGICAL PROJECT AND ITS INTER-RELATIONSHIP WITH THE PRINCIPLES OF DEMOCRATIC MANAGEMENT: an analysis in a municipal public school of São Luís – MA”. The research has as primary objective: to analyze the process of updating the Political Pedagogical Project of a municipal public school in São Luís - MA, identifying the established interrelation of this process with the principles of Democratic Management. In order to achieve this proposal, it is defined as secondary objectives: to present a historical clipping on the transition from school administration towards Democratic Management, in view of the historical, political and economic conditions that interfered in this process; to know the concepts of Democratic Management that underlie the materiality of Pedagogical Political Projects, having as criteria the principles of autonomy, participation and decentralization; discuss the pedagogical, political and methodological assumptions that guide the updating of the Political Pedagogical Project and produce a training proposal with the purpose of assisting in the construction or updating of the Political Pedagogical Project based on the principles of Democratic Management. By developing a State of Knowledge, it was possible to consolidate some authors that guided the research, such as: Alarcão (2001); Cury (2002; 2013 and 2015); Demo (1985; 1995; 1997 and 1999); Dourado (2004; 2006 and 2007); Drabach (2009; 2010 and 2013); Ferreira (2004 and 2009); Gadotti (1994; 1997 and 2000); Time (2012); Libâneo (2012; 2013 and 2015); Luck (1991; 1997; 2009; 2013a;2013b and 2017); Oliveira (2004; 2014 and 2015); Paro (1993; 1998; 2007; 2012 and 2016); Rosar (2001; 2012; 2015 and 2017); Veiga (2003; 2009; 2013 and 2019); Vasconcellos (2002 and 2019). The adopted methodology has a qualitative approach, with the dialectical analysis method, it also has a descriptive and explanatory analysis procedure and was carried out in the case study format. Regarding the construction of the research, a survey of bibliographic and documentary references was used. In the context of the field research, the data collection instruments were structured interviews, questionnaires and a focus group, and the target audience of these instruments was a group of teachers, management, the pedagogical monitoring technique of the network and parents. Regarding the definition of the researched institution, it was a school (more specifically an annex), which is part of the public education network of São Luís - MA, which works with students in the early years of elementary school. Regarding the data analysis, the content analysis procedure was used in order to seek the meanings of the speeches and responses obtained. The research had six sections, the first is the introduction, the second section deals with the modification of the paradigm of school administration towards Democratic Management and the context of redemocratization in Brazil, the third deals with an analysis of the theme of democratic management, the fourth deals with the aspects that make up the Political Pedagogical Project, the fifth focuses on the analysis of the results of the field research, the sixth brings the conclusions of the current study. The results obtained reveal that the PPP theme still faces fundamental difficulties for implementation in the school context. It is also noteworthy that the research has the construction of a Pedagogical Product, this is a proposal for training with the topics covered in the context of the research